MENALAR URGENSI PENGHAPUSAN UJIAN NASIONAL DEMI KEADILAN SISWA, GURU DAN SEKOLAH PASCA PUTUSAN MAHKAMAH AGUNG NOMOR: 2596 K/PDT/2008 - Aufi Imaduddin (PREMIERE : Journal of Islamic Elementary Education, 2019)
The national exam is a form of national level learning evaluation that has been set by the government to determine student learning outcomes. However, in the implementation of the national exam has a negative impact on students, teachers and schools. So lately there has been a renewed discourse about the elimination of the national examination, it began with the policy of the Indonesian Minister of Education and Culture to abolish the national examination in 2021. Especially if we examine further that legal efforts to stop the implementation of the national examination have existed since 2006 and the peak in 2009 was the decision of the Supreme Court number: 2596 K / PDT / 2008 which in essence required the government to stop the implementation of the national examination before resolving various existing problems. Therefore, the writer is interested in asking logically to think about the urgency of abolishing the national exam after the decision of the Supreme Court. In this paper, the method used by the author is a qualitative method based on social facts that occur based on juridical reasons based on the laws and regulations related to research. The results of this study found that the implementation of the national exam has claimed justice for students in obtaining their human rights in obtaining education that has been mentioned in the 1945 Constitution and is not in accordance with educational thought according to Ki Hajar Dewantara, as well as causing various depressive pressures which have an impact on their minds stressed and suicidal students. The implementation of national exams has also revoked justice for teachers, where teachers in their teaching are supposed to educate students well and develop their students' thinking instincts, with the national examination the teacher only drills students to memorize and do exercises that lead to the national exam. Recalling also that the implementation of national examinations in a juridical manner in the decision of the Supreme Court has violated various laws and regulations regarding education in Indonesia. Therefore, the elimination of the national exam will give back the right to justice for students, teachers and schools according to their respective proportions.